Stabilization and Regulation of Nonlinear Systems A Robust and Adaptive Approach - Chen, Zhiyong; Huang, Jie.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The core of this textbook is a systematic and self-contained treatment of the nonlinear stabilization and output regulation problems. Its coverage embraces both fundamental concepts and advanced research outcomes and includes many numerical and practical examples. Several classes of important uncertain nonlinear systems are discussed. The state-of-the art solution presented uses robust and adaptive control design ideas in an integrated approach which demonstrates connections between global stabilization and global output regulation allowing both to be treated as stabilization problems. Stabilization and Regulation of Nonlinear Systems takes advantage of rich new results to give students up-to-date instruction in the central design problems of nonlinear control, problems which are a driving force behind the furtherance of modern control theory and its application. The diversity of systems in which stabilization and output regulation become significant concerns in the mathematical formulation of practical control solutions$1 (Bwhether in disturbance rejection in flying vehicles or synchronization of Lorenz systems with harmonic systems$1 (Bmakes the text relevant to readers from a wide variety of backgrounds. Many exercises are provided to facilitate study and solutions. Striking a balance between rigorous mathematical treatment and engineering practicality, Stabilization and Regulation of Nonlinear Systems is an ideal text for graduate students from many e ngineering and applied-mathematical disciplines seeking a contemporary course in nonlinear control. Practitioners and academic theorists will also find this book a useful reference on recent thinking in this field.s
Introduction -- Fundamentals of Nonlinear Systems -- Classification of Nonlinear Control Systems -- Robust Stabilization -- Adaptive Stabilization -- Universal Adaptive Stabilization -- Robust Output Regulation: A Framework -- Global Robust Output Regulation -- Output Regulation with Uncertain Exosystems -- Attitude Control of a Rigid Spacecraft -- Appendix.
Keywords: Engineering; System theory; Control engineering; Engineering; Control; Systems Theory, Control; Electronic books